Dual colorimetric sensor for picric acid and pyrophosphate: Practical application for molecular logic gates. (July 2019) - Kumar, Pawan; Arya, Dheeraj; Nain, Deepak; Singh, Ajeet; Ghosh, Amrita; Jose, D. Amilan
Abstract: Simultaneous recognition of two different analytes such as picric acid or trinitro phenol (TNP) and pyrophosphate (PPi) by using the Dabsyl derivative1 has been reported. TNP was detected by1 with a remarkable red shift of 60 nm in the absorption spectra along with a color change from yellow to red. Biological important anion PPi was detected by color and UV–Vis absorption spectrum. Usually, multiple analytes can be detected either by sequential or simultaneous recognition by analytes having counter attraction such as anion-cation or acid-base. Here we have described the detection of two different analytes PPi and TNP, they do not have any counter-attraction. TNP can be detected with a detection limit of 7.2 × 10 −6  M and PPi could be detected with LOD of 2.01 × 10 −5  M in solution. The interaction between the TNP -OH group and the -N(CH3 )2 group of receptors1 plays a very important role in the detection of TNP. Anion PPi can be detected through hydrogen bond interaction between the sulfonamide group of1 and PPi. To the best of our knowledge for the first time, we have used the dabsyl based receptor for the detection of TNP or picric acid. Receptor1 was also explored for the construction of molecular logic gates such as AND and INHIBIT by using two analytes PPi and TNP. Graphical abstract: Image 1 Highlights: Dual colorimetric sensor1 for trinitro phenol (TNP) and pyrophosphate (PPi) has been reported. It is highly selective for picric acid or TNP. Limit of detection for TNP is 1.48 × 10 −5  M. The interaction between the -OH group of TNP and the -N(CH3 )2 group of1 is responsible for the selective detection of TNP. PPi and TNP detection by1 also applied for the construction of AND and INHIBIT molecular logic gates.